2015
DOI: 10.1016/j.ijsu.2015.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence after Le Fort colpocleisis for severe pelvic organ prolapse in elderly women

Abstract: Objective and subjective cure rates of Le Fort colpocleisis for the treatment of severe POP were high with low morbidity. Parameters associated with prolapse recurrence were longer postoperative vaginal length and wider genital hiatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
0
21
1
2
Order By: Relevance
“…Krissi et al showed 19.1% of recurrence in their series of 47 patients and analyzing different parameters attributed increased risk to cases with higher total vaginal length (TVL) and increased genital hiatus (GH); possibly suggested that recurrence would be linked to greater difficulty in obliteration of the vagina. 12 They observed GH and TVL mean values of 4.6 and 9.5 respectively and the recurrence group showed GH mean of 5.1 and TVL mean of 8.9. Our patient that presented recurrence had GH = 4 and TVL=7; but the average of GH and TVL in the whole sample were 5 and 8.5, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Krissi et al showed 19.1% of recurrence in their series of 47 patients and analyzing different parameters attributed increased risk to cases with higher total vaginal length (TVL) and increased genital hiatus (GH); possibly suggested that recurrence would be linked to greater difficulty in obliteration of the vagina. 12 They observed GH and TVL mean values of 4.6 and 9.5 respectively and the recurrence group showed GH mean of 5.1 and TVL mean of 8.9. Our patient that presented recurrence had GH = 4 and TVL=7; but the average of GH and TVL in the whole sample were 5 and 8.5, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Out of the remaining 38 articles only 23 were based on studies focusing on colpocleisis or colpectomy and related surgical techniques or outcome measures. Some reports focused on clinical outcomes following partial Neugebauer-Le Fort colpocleisis, total colpocleisis or partial colpectomy [1][2][3][4][5][6][7][8][9][10]. These papers dealt mainly with objective or subjective cure rates after prolapse surgery.…”
Section: Resultsmentioning
confidence: 99%
“…So far, all reports focused on surgical techniques preserving the integrity of the suburethral tissue (usually the first 3cm of the anterior vaginal wall), even when total colpectomy was performed for pelvic organ prolapse [4,5,11,12]. Some authors reported on combined prolapse and incontinence surgery, where up to 100% of their patients underwent concomitant midurethral sling placement at time of colpocleisis [1,9,13,14]. The incidence of de novo urinary incontinence -if at all quoted -varied between 0-27% [3,4,10,11].…”
Section: Resultsmentioning
confidence: 99%
“…- vaginal anterior e posterior, suturando-se a parede anterior com a posterior da vagina, obliterando-se parcialmente seu lúmen (KRISSI et al, 2015).…”
Section: Tratamento Cirúrgico E Conservador De Prolapsos De óRgãos Péunclassified